Brain literacy empowers educators to meet diverse learner needs. (3rd July 2019) - Walker, Zachary; Hale, James B.; Annabel Chen, Shen-Hsing; Poon, Kenneth
ABSTRACT: The potential of educational neuroscience in teacher training and continuing professional development has been debated extensively, yet knowledge translation is largely absent in this field. Without objective methods for translating and disseminating educational neuroscience evidence, the impact of training on educators and the children they serve will remain limited. This position paper addresses this critical teacher education need by providing a rationale for why brain literacy training is vital as teachers learn to meet the needs of diverse learners. The authors offer three important factors for consideration regarding the utility of educational neuroscience for educators and allied school practitioners. First, the foundations and history of professional educator development in educational neuroscience will be considered. Second, a brief review of the empirical learning science literature within the context of science-based education will be considered. Third, a rationale for including a more intensive brain literacy training for educators is provided by comparing the impact traditional teaching practices and brain literate strategies have on curriculum and instruction, and how standard practices may actually undermine student brain development. Finally, three recommendations for developing educator brain literacy are offered to guide future policy, research, and practice decisions.